PENGARUH KONDISI KEUANGAN DAN NON KEUANGAN TERHADAP PENERIMAAN OPINI GOING CONCERN PADA PERUSAHAAN MANUFAKTUR DI BEI - Andi Kartika (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2012)
This research is a study that tested the effect of Financial Condition, Audit Quality, Audit Opinions ofPrior Year, the Company’s Growth, Opinion Shopping of the acceptance of Going Concern in themanufacturing companies listed at Indonesia Stock Exchange. In this study, researchers usedpurposive sampling and sample size to obtain a sample of 80 manufacturing companies listed on theStock Exchange in the year 2006-2009. The method of analysis used was logistic regression. Theresults of this study indicate Financial Condition, audit quality and Opinion Shopping do not affect thegoing concern opinion reception while the previous year's audit opinion and the Company Growtheffect on the acceptance of going-concern opinion.This study’s limitation is the study sampling periodis only 4 years old so not ideal for seeing a trend of the influence of financial condition other models,like another Alman Model Revisi. Therefore advisable to consider for using other main variable andbanking company as research source in the future studies to discover the difference.Keywords: Going Concern, Financial Condition, Quality Audit, Audit Opinions Prior Year, CompanyGrowth, Opinion Shopping